Negative thermal expansion of HTSC-type structures:low temperature structure measurementson Eu1+x(Ba1-yRy)2-xCu3O7-d compounds and theoretical treatment - Eremenko, V.V.; Feodosyev, S.B.; Gospodarev, I.A.; Sirenko, V.A.; Shvedun, M.Yu.; McCallum, W.; Tovar, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The temperature dependences of the lattice parameters were investigated on the perovskite-likestructures Eu1+x(Ba1-yRy)2-xCu3O7-d with Ba substitution by light rare earth, using x-ray diffraction techniques. A negative thermal expansion effect was observed and explained in detail.